(untitled) (Italian Review of Legal History, 2017)
In Romano-canonical procedure, confessed criminals could not be examined on their accomplices, except for enormous crimes. In these cases, however, twelfth- and thirteenth-century canonists disagreed about the probative value of these statements. According to some jurists they could be deemed as a full proof, while others held that they only counted as a presumption. Nevertheless, from the thirteenth century the doctrine reached a consensus that the statements of the defendants had to be further corroborated in order to have effect. These principles were also confirmed in the inquisitorial procedure against heresy. This essay, providing a survey of the manuscripts, reconstructs the stages of the debate on this topic, distinguishing among the contribution of the Anglo-Norman, Parisian and Bolognese schools.